1995
DOI: 10.1093/genetics/140.2.703
|View full text |Cite
|
Sign up to set email alerts
|

An autosomal genetic linkage map of the sheep genome.

Abstract: We report the first extensive ovine genetic linkage map covering 2070 cM of the sheep genome. The map was generated from the linkage analysis of 246 polymorphic markers, in nine three-generation full-sib pedigrees, which make up the AgResearch International Mapping Flock. We have exploited many markers from cattle so that valuable comparisons between these two ruminant linkage maps can be made. The markers, used in the segregation analyses, comprised 86 anonymous microsatellite markers derived from the sheep g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 305 publications
(19 citation statements)
references
References 74 publications
0
19
0
Order By: Relevance
“…Mate choice on the basis of MHC type was analysed using ¢ve polymorphic microsatellite loci located within or adjacent to the MHC in recent ovine genetic maps (Crawford et al 1995) as shown in ¢gure 1. The markers OLADRB and OLADRBps are located within MHC class II expressed and non-expressed genes respectively (Blattman & Beh 1992;Schwaiger et al 1993), OMHC1 is located within the MHC class I region (Groth & Wetherall 1994) and BM1815 and BM1818 (Bishop et al 1994) were used as £anking marker controls.…”
Section: (D) Mhc Markersmentioning
confidence: 99%
“…Mate choice on the basis of MHC type was analysed using ¢ve polymorphic microsatellite loci located within or adjacent to the MHC in recent ovine genetic maps (Crawford et al 1995) as shown in ¢gure 1. The markers OLADRB and OLADRBps are located within MHC class II expressed and non-expressed genes respectively (Blattman & Beh 1992;Schwaiger et al 1993), OMHC1 is located within the MHC class I region (Groth & Wetherall 1994) and BM1815 and BM1818 (Bishop et al 1994) were used as £anking marker controls.…”
Section: (D) Mhc Markersmentioning
confidence: 99%
“…Cross-species amplification of microsatellite loci has been reported within closely related livestock species [3,28,37] and has been exploited in the construction of genetic maps for cattle [17], sheep [9], and goats [42] in the Bovidae family. Exchanges of microsatellite markers have also been observed between related avian species [8,29,30,34].…”
Section: Introductionmentioning
confidence: 99%
“…The United States Meat Animal Research Center (USMARC) and other US researchers were involved and contributed to the international mapping flock to create linkage maps (Crawford et al . 1995 ; de Gortari et al . 1998 ; Maddox et al .…”
Section: Progression Of Genomicsmentioning
confidence: 99%